The relationship between organizational trust and voice behavior among neonatal intensive care unit nurses in tertiary A hospitals in Sichuan Province: the mediating role of career resilience - Zhang, Xiujuan; Huang, Xi; Hu, Yanling; Chen, Qiong; Zhao, Xiufang (Frontiers in Public Health, 2024)
BackgroundNeonatal intensive care unit (NICU) nurses face immense pressure, yet research on their voice behavior and the motivational mechanisms behind it is limited. Specifically, the impact of organizational trust and career resilience on this behavior has not been thoroughly explored.AimThis study aims to examine the relationship between organizational trust and voice behavior in NICU nurses, with career resilience acting as a mediating factor, providing empirical evidence for nursing management.MethodsA multicenter cross-sectional survey was conducted from January to June 2023, involving 422 neonatal nurses from tertiary hospitals in Sichuan Province, China. Data were collected using a self-designed questionnaire, a voice behavior scale, an organizational trust scale, and a career resilience scale. Hierarchical regression and structural equation modeling (SEM) were employed to analyze the relationships among the variables.ResultsHierarchical regression analysis revealed that organizational trust (β = 0.28, p < 0.001) and career resilience (β = 0.45, p < 0.001) significantly predicted voice behavior. Mediation analysis using structural equation modeling confirmed that career resilience mediated the relationship between organizational trust and voice behavior, with a mediation effect of 0.340, accounting for 44.8% of the total effect. The structural model demonstrated good fit indices (CFI = 0.962, RMSEA = 0.045), indicating the robustness of the proposed model.ConclusionOrganizational trust significantly influences NICU nurses’ voice behavior, with career resilience playing a critical mediating role. Enhancing organizational trust and fostering career resilience among NICU nurses can improve their willingness to engage in voice behavior, ultimately leading to better healthcare outcomes.Implications for nursing managementNursing managers should foster a trusting and supportive work environment to improve nurses’ job satisfaction and organizational commitment. This can be achieved by enhancing psychological empowerment and promoting positive interactions between nurses, the organization, and leadership. Such an environment helps reduce burnout and strengthens career resilience. Increased resilience enables nurses to better manage clinical pressures and challenges, elevating their career expectations and enhancing their willingness to engage in work. This, in turn, promotes innovation, active participation, and improved voice behavior, ultimately contributing to organizational success.